Long-term ecological and socio-economic Changes in and around bwindi impenetrable National park, south-western Uganda - Kasangaki, A.; Bitariho, Robert; Shaw, P.; Robbins, M; McNeilage, A (The ecological impact of long-term changes in Africa’s rift valley, 2012)
Bwindi Impenetrable National Park is a UNESCO World Heritage Site and is well known among conservationists because of its unique biodiversity that includes approximately half the world’s population of mountain of gorillas. The extremely high human population density around the forest (200-300 people km-2), coupled with a history of forest degradation through logging and other forms of human disturbance, has resulted in significant challenges to its conservation. When Bwindi was gazetted as a national park in 1991 there were extremely high levels of conflict between park staff and local communities, but over the intervening two decades there has been a very large investment in the conservation of this forest. In this chapter we review the available evidence of the long term changes in the forest habitats and wildlife over that period.
Keywords: National Park; Heritage Site; Conservationists; Gorillas; Uganda